Evaluating agricultural decision-making: A systematic review of discrete choice experiments and producers' preferences - Jaba Rani Sarker; Siddhartha Shankar Roy; Mallika Roy (World Development Sustainability)
Producers’ preferences are considered one of the key concerns that can be steered to formulate policies in crop farming. However, despite the extensive body of literature available on producers’ preferences and their drivers, producers’ preferences for specific crop farming have received less attention. This systematic review synthesizes findings from 14 primary studies that utilized discrete choice experiments (DCEs) to assess farmers' preferences and willingness to pay (WTP) for various crop attributes. The review employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to select the relevant articles. This systematic review identifies key attributes influencing crop choices, including agronomic factors, market conditions, socio-demographic characteristics, and risk perceptions. The findings reveal that farmers prioritize yield stability, pest resistance, and market access when selecting crops, with WTP varying across different farming contexts. Moreover, economic and environmental risks significantly shape decision-making, emphasizing the need for policies that align with producers’ preferences. These insights can guide policymakers, researchers, and agribusinesses in developing targeted interventions that promote sustainable and profitable agricultural practices.